Factors related to the onset of postpartum ovarian activity in dual purpose cattle in the tropics - Rubio, I.; Corro, M.; Castillo, E.; Galindo, L.; Aluja, A.; Galina, C.; Murcia, C. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
In order to determine the factors related with the reproductive performance (days to first progesterone rise, to first oestrus, to conception and services per conception) and milk yields with pasture attributes (standing forage biomass and crude protein content), blood metabolites (total protein, albumin, urea, betahydroxybutyrate and globulin) and body condition changes, a total of 165 crossbred cows Bos indicus x Bos taurus that calved within the period of study were used on 12 small farmers located within north-central region of the state of Veracruz, México. Each farm was visited every month. Milk samples were collected twice a week for progesterone analysis. Blood samples and body condition score were taken once a month. ANOVA was used to detect the effect of farm, season and their interaction upon all response variables. Regression and correlation procedures were used to quantify those relationships. Neither changes in body condition score or pasture attributes were sensitive enough to predict either milk yield or reproductive performance. Blood metabolite profiles were not consistently related to productive or reproductive variables either. On the other hand, the effects of farm and season were significant (P < 0.05) on almost all response variables.